Factors Affecting the Investment Behavior of Generation X and Generation Z - Thawong, Thitiworada; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (My University, 2026)
While types of cohort generally build their different patterns of attitudes by certain conditioning forces—a social-economic-technical environment; this study tries to evaluate how two specific generations, namely X and Z, are always different from each other as far as the generational-determining forces are concerned into the investment behavior of these two groups. The qualitative study design involves the use of an item answering through set structured questionnaire items to measure the four latent variables out of the twenty-three items included. Three other well-known professionals validated the expert ratings concerning the perceived effectiveness of the questionnaires in that the item interrogated had Index of Item-Objective Congruency values above the requirement of 0.5. Through a pilot survey with a sample of 30 respondents, all constructs gave Cronbach's alpha coefficients over 0.7 with the use of the SPSS software program indicating that the degree of internal consistency and reliability of the research instrument was high in quality. Data resulted from SPSS analysis revealing a very high score in Cronbach’s alpha, exceeding 0.7 for all constructs that indicate internal consistency and reliability of the instrument. Therefore, understanding the factors that influence investment decisions across the two generations could well broaden and deepen the understanding of the currents that govern today’s financial behavior.
Keywords: Generation X; Generation Z; Investment factors; Investment knowledge and investment experience factor; PEST factors; Risk perception factor